2011 16th International Solid-State Sensors, Actuators and Microsystems Conference 2011
DOI: 10.1109/transducers.2011.5969868
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric PDMS films for power MEMS

Abstract: We have successfully demonstrated the fabrication of piezoelectric PDMS films utilizing casting, stacking, and micro plasma discharge processes. To realize electromechanical sensitivity, PDMS structures with micrometer-sized cells are implanted with positive and negative charges on the opposite internal surfaces of each cell, which behaves just like a dipole. In the prototype demonstration, multilayer PDMS films with inner cells of 50×50×50 μm 3 are fabricated and charged under electric fields up to 40 MV/m. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…We note that the capacitor structure formed by the PDMS films may also generate a voltage response upon bending. It has been reported that if a 10 kV poling voltage is applied to induce local dipoles in a PDMS layer, PDMS may exhibit a piezoelectric coefficient d 33 of 350 pC/N. In contrast, our BaTiO 3 devices involve no poling because the BaTiO 3 layer is intrinsically polar.…”
Section: Resultsmentioning
confidence: 89%
“…We note that the capacitor structure formed by the PDMS films may also generate a voltage response upon bending. It has been reported that if a 10 kV poling voltage is applied to induce local dipoles in a PDMS layer, PDMS may exhibit a piezoelectric coefficient d 33 of 350 pC/N. In contrast, our BaTiO 3 devices involve no poling because the BaTiO 3 layer is intrinsically polar.…”
Section: Resultsmentioning
confidence: 89%